Acute Oral Toxicity Test of Antihypertensive Polyherbal Preparations Containing Allium sativum Curcuma aeruginosa & Amomi fructus - Herzan Marjawan; Woro Rukmi Pratiwi; Dwi Aris Agung Nugrahaningsih; Eti Nurwening Sholikhah; Pamungkas Bagus Satriyo (Majalah Farmaseutik, 2022)
Hypertension is a major factor causing atherosclerotic cardiovascular disease, heart failure, stroke, and kidney failure. Polyherbal preparations containing garlic (Aliium sativum), temu ireng (Curcumae aeruginosae) and cardamom (Amomi fructus) have been widely used to treat hypertension. Despite widely used in community, its safety has not been evaluated. This study aimed to evaluate the single dose oral safety of the polyherbal. The acute oral toxicity test was done using fixed dose methods. Single dose of the polyherbal was administered to female Wistar rats. The clinical examination was done after administration of the polyherbal and continued until the 14th day to check for symptoms of toxicity, changes in body weight. On day 15, the animal was sacrificed and histopathological examination was conducted. The body weight did not differ between animal that received polyherbal and not received polyherbal. However, there was an increase in body weight in a group that received polyherbal at a dose of 2000 mg/kg. The absolute and relative organs weight was also similar among groups. There were no macroscopic and histopathological changes in kidney, liver, heart, spleen, aorta, and lungs. The polyherbal preparations containing Aliium sativum, Curcumae aeruginosae and Amomi fructus is safe with LD50 >2000-5000 mg/kg in Wistar rats.